Accurate vessel width measurement from fundus photographs: a new concept. Issue 1 (January 1994) - Rassam, S M; Patel, V; Brinchmann-Hansen, O; Engvold, O; Kohner, E M
Abstract : Accurate determination of retinal vessel width measurement is important in the study of the haemodynamic changes that accompany various physiological and pathological states. Currently the width at the half height of the transmittance and densitometry profiles are used as a measure of retinal vessel width. A consistent phenomenon of two 'kick points' on the slopes of the transmittance and densitometry profiles near the base, has been observed. In this study, mathematical models have been formulated to describe the characteristic curves of the transmittance and the densitometry profiles. They demonstrate the kick points being coincident with the edges of the blood column. The horizontal distance across the kick points would therefore indicate the actual blood column width. To evaluate this hypothesis, blood was infused through two lengths of plastic tubing of known diameters, and photographed. In comparison with the known diameters, the half height underestimated the blood column width by 7.33% and 6.46%, while the kick point method slightly overestimated it by 1.40% and 0.34%. These techniques were applied to monochromatic fundus photographs. In comparison with the kick point method, the half height underestimated the blood column width in veins by 16.67% and in arteries by 15.86%. The characteristics of the kick points and their practicality have been discussed. The kick point method may provide the most accurate measurement of vessel width possible from these profiles.